Measuring polycentric structures of megaregions in China: Linking morphological and functional dimensions. (October 2021) - Chen, Wei; Golubchikov, Oleg; Liu, Zhigao
The idea of megaregions, which focuses on polycentricity, competitiveness, and integration attracts much attention in research and policy. China has used megaregions as a normative governance framework that leverages polycentric regional development for balancing economic competitiveness and spatial development. This paper explores to what extent these megaregions actually reveal polycentric versus monocentric structures. The analysis demonstrates a divergence between the morphological and functional organization of China's megaregions. Five types of megaregions are identified as per the relationships between the morphological and functional dimensions. Functionally, the Pearl River Delta, Shandong Peninsula, and Yangtze River Delta are among the most polycentric megaregions. The majority of others, even where morphologically polycentric, do not exhibit high degrees of functional polycentricity. The study demonstrates a problematic nature of megaregions as a governance agenda for regional polycentricity. It argues that if China genuinely wants to achieve greater levels of polycentricity and spatial cohesion, differentiated policies should be implemented for megaregions.